Prediktor Kesulitan Intubasi: Perbandingan Antara Rasio Tinggi Badan Terhadap Jarak Tiromental, Skor Mallampati Dan Jarak Tiromental - Riyadh Firdaus; Aries Perdana; Rinal Effendi (Majalah Kedokteran Indonesia, 2023)
Introduction: The Mallampati score and thyromental distance (TMD) are frequently used to identify challenging laryngoscopies, but their reliability in predicting difficulty is uncertain. This study aims to assess the effectiveness of using the ratio of height to thyromental distance (RHTMD) in predicting difficult visualization of the larynx (DVL) when compared to the Mallampati score and TMD.Method: To achieve this goal, 277 patients who received general anesthesia during elective surgery were evaluated using the Mallampati score, TMD, and RHTMD. The Cormack and Lehane (CL) classification was used to grade the laryngeal view, with CL grade 3 and 4 indicating difficult visualization. The study then determined and compared the area under the curve (AUC), sensitivity, and specificity for each airway predictor.Results: The AUC of RHTMD (85.5%) was better than TMD (82.7%) and significantly better than the Mallampati score (61.4%).Conclusion: RHTMD is more accurate in predicting difficult laryngoscopy than both the Mallampati score and TMD.